Callicarpa stoloniformis (Lamiaceae), a new species from Southeast China based on morphological characters and phylogenetic evidence - Zhonghui Ma; Xiangxiu Su; Huimin Cai; Zhiwei Su; Bin Chen (Ecology and Evolution, 2023)
Abstract Callicarpa stoloniformis sp. nov. (Lamiaceae) is described as a new species from Fujian Province of China on the basis of both morphological and molecular data. The new species is morphologically most close to C. hainanensis. However, it can be distinguished from the latter by its unique procumbent life form, adventitious roots at nodes, papery leaves, cup‐shaped or campanulate calyx, truncate or shallow fissure calyx lobes, and smaller fruits. In addition, the new species is also similar with C. basitruncata, a species only known from the original description and the photograph of holotype, but it can differ from the latter by its procumbent shrub, purple terete branchlets with apparent linear lenticels, adventitious roots at nodes, and papery larger leaves with prominently cordate leaf base. Original photographs, illustration, distribution map, and a comparative morphological table, as well as an identification key of the related taxa are provided.